Regenerative topical skincare: stem cells and exosomes - Taub, Amy Forman (Frontiers in Medicine, 2024)
Regenerative medicine and its offshoot, regenerative aesthetics, have been hot topics over the past 15 years. Studies with heterochronic parabiosis and others pointed to a circulating factor that could rejuvenate aging tissues. Stem cells are known to have regenerative powers, but they are difficult to extract, grow in culture or maintain. Exosomes (EVs), extracellular vesicles from 30-150 nm, have been discovered to be a primary form of communication between tissues. Using stem cell supernatants to generate desirable EVs has become a heralded treatment for aesthetic treatments. Preclinical studies with EVs show many benefits including improving the function of fibroblasts and healing wounds more rapidly. Clinical studies with EVs in aesthetics are very few. Thus, the excitement generated by EVs should be tempered with realism about the lack of available treatment products as well as the lack of scientific proof.